Pathogenic bacteria significantly increased under oxygen depletion in coastal waters: A continuous observation in the central Bohai Sea - Guo, Yiyan; Wu, Chao; Sun, Jun (Frontiers in Microbiology, 2022)
TThe spread of pathogenic bacteria in coastal waters endangers the health of the local people and jeopardizes the safety of the marine environment. However, their dynamics during seasonal hypoxia in the Bohai Sea (BHS) have not been studied. Here, pathogenic bacteria were detected from the 16S rRNA gene sequencing database and were used to explore their dynamics and driving factors with the progressively deoxygenating in the BHS. Our results showed that pathogenic bacteria were detected in all samples, accounting for 0.13% to 24.65% of the total number of prokaryotic sequences in each sample. Pathogenic Proteobacteria was dominated in all samples, followed by Firmicutes, Actinobacteria, Tenericutes, and Bacteroidetes, etc. β-diversity analysis showed that pathogenic bacteria are highly temporally heterogeneous and regulated by environmental factors. According to RDA analysis, these variations may be influenced by salinity, ammonia, DO, phosphate, silicate, and Chl a. Additionally, pathogenic bacteria in surface water and hypoxia zone were found to be significantly separated in August. The vertical distribution of pathogenic bacterial communities is influenced by several variables, including DO and nutrition. It is noteworthy that the hypoxia zones increase the abundance of certain pathogenic genera, especially Vibrio and Arcobacter, and the stability of the pathogenic bacterial community increased from May to August. These phenomena indicate that the central Bohai Sea is threatened by an increasingly serious pathogenic community from May to August. And the developing hypoxia zone in the future may intensify this phenomenon and pose a more serious threat to human health. This study provides new insight into the changes of pathogenic bacteria in aquatic ecosystems and may help to make effective policies to control the spread of pathogenic bacteria.